Autotaxin Structure Activity Relationships Revealed through Lysophosphatidylcholine Analogs - North, E. Jeffrey (2009)
Autotaxin (ATX) catalyzes the hydrolysis of lysophosphatidylcholine (LPC) to form the bioactive lipid lysophosphatidic acid (LPA). LPA stimulates cell proliferation, cell survival, and cell migration and is involved in obesity, rheumatoid arthritis, neuropathic pain, atherosclerosis and various cancers, suggesting that ATX inhibitors have broad therapeutic potential. Product feedback inhibition of ATX by LPA has stimulated structure activity studies focused on LPA analogs. However, LPA displays mixed mode inhibition, indicating it can bind to both the enzyme and the enzyme-substrate complex. This suggests that LPA may not interact solely with the catalytic site. In this report we have prepared LPC analogs to help map out substrate structure activity relationships. The structural variances include length and unsaturation of the fatty tail, choline and polar linker presence, acyl versus ether linkage of the hydrocarbon chain, and methylene and nitrogen replacement of the choline oxygen. All LPC analogs were assayed in competition with the synthetic substrate, FS-3, to show the preference ATX has for each alteration. Choline presence and methylene replacement of the choline oxygen were detrimental to ATX recognition. These findings provide insights into the structure of the enzyme in the vicinity of the catalytic site as well as suggesting that ATX produces rate enhancement, at least in part, by substrate destabilization.